Differential operators specifying the solution of an elliptictype iterated equation - Aleksandrovich, I. N.; Sidorov, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
We construct differential operators that transform arbitrary holomorphic functions into regular solutions of elliptic-typeequations of the second and higher orders. The Riquier problem is solved for the elliptic-type equation of the fourth order.